• Matéria: Matemática
  • Autor: Aninhagf
  • Perguntado 7 anos atrás

-2x ^ 2 - 5x + 6 = 0

Respostas

respondido por: Anônimo
1
-2x^2-5x+6=0

∆=b^2-4.a.c

∆=(-5)^2-4.(-2).(6)

∆=25+48

∆=65

x'=5+√65/2.(-2)

x'=5+√65/-4

x'=- 5+√65/4

x"=-5-√65/4

s={-5+√64/4;-5-√65/4}


espero ter ajudado!

boa tarde!
respondido por: cfilippo
1

Resposta:

-2x²-5x+6=0

2x²+5x-6=0

x= (-5 +-V 25 -4*2*-6)/2*2

X=(-5+- V 25+ 48 )/4

x= (-5+- V73)/4

x'= (-5+V73)/4

x''= (-5-V73)/4

Explicação passo-a-passo:



Aninhagf: Muitooooo obrigada ♡
Perguntas similares